Social Media: A New Communication Medium in Marketing - Malhotra , Sharad (Gyan Management Journal, 2016)
Social media as the name indicates is the best way to socialize in the world. It is in fact the major tool today used by any organization to communicate with the consumer about the products. Big companies do branding through it for improving their market share. It is a new trend of communication that has come up and has modified the behaviour of firm and consumer in the market. Many companies think their existence on social media network as a strong base for their success in the market. From one perspective it is clear that social media is of utmost use to communicate between businesses to business (B to BJ and from business to customer (B to CJ most efficiently and effectively. To many business organizations it has proved to be the boon that has created huge brand awareness and the business revenue in this operation. This new approach is not only brand awareness but also a trust among the new customers. The change in the thinking of the customer, the purchasing style he feel mostly related to the market through this new tool. People share their views and in today's trend it has not only become the marketing tool but a major platform to communicate the voice of the people. From producer's aspect it has developed as a tool that reaches to the customer beyond its imagination and at the same time it has given consumer the freedom and liberty to examine the products carefully and critically. This study aims to study the impact of social media in the market. How it has helped the managements to market their products and the relevance of social media in today's life.
Keywords: Social media; marketing; benefits of social media